Synthesis of Zinc Oxide-based nanocomposites for photocatalytic removal of contaminant - Maryam Tondkar Mobaraki; Hassan Zavvar Mousavi; Hadi Fallah Moafi; Mohammad Moghadam (شیمی کاربردی روز)
In this research, zinc oxide nanoparticles were synthesized by the chemical precipitation method, and graphite carbon nitride was synthesized by the thermal decomposition method. Nanocomposites of zinc oxide co-doped with g-C3N4 were prepared using the Ultrasonic method. The samples were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), Fourier transform infrared spectroscopy (FT-IR), and diffuse reflectance spectroscopy (DRS). The XRD results revealed that zinc oxide and graphite carbon nitride have a hexagonal wurtzite structure and a hexagonal structure, respectively. It was found that the particle size of the ZnO/g-C3N4 nanocomposite was less than 100 nm. The effect of operational parameters such as concentration of doping elements, photocatalyst dosage, pH, initial concentration of Methylene Blue, effect of oxidants, and irradiation time on the extent of degradation was investigated. The photocatalytic activity of the undoped ZnO, g-C3N4, and ZnO/g-C3N4 nanocomposite photocatalysts were evaluated by the photocatalytic degradation of methylene blue in an aqueous solution. The results show that the photocatalytic activity of the ZnO/g-C3N4 photocatalyst is much higher than that of undoped ZnO. The cooperation of the g-C3N4 leads to the narrowing of the band gap and greatly improves the photocatalytic activity. The ZnO/g-C3N4 photocatalyst 15 mol% shows the best photoactivity and photodecomposition efficiencies were improved by 95% under Visible irradiation approximately compared with the pure ZnO sample.